2007
DOI: 10.1111/j.1574-6976.2006.00060.x
|View full text |Cite
|
Sign up to set email alerts
|

A surveillance network for meningococcal disease in Europe

Abstract: Between 1999 and 2004, the European Union Invasive Bacterial Infections Surveillance Network (EU-IBIS) received c. 50,000 reports of meningococcal disease from 27 participating countries. Analysis has demonstrated a major decline in the incidence of invasive disease in those countries that have introduced routine vaccination against serogroup C infection. The establishment of rapid reporting of W135 and B2a/B2b strains has been able to provide early reassurance that these strains are not emerging as major publ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

14
92
2
1

Year Published

2008
2008
2016
2016

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(109 citation statements)
references
References 25 publications
14
92
2
1
Order By: Relevance
“…7,25,26 The development of a sufficiently immunogenic vaccine to broadly protect infants from meningococcal disease has proven challenging. Recent studies in this vulnerable population have demonstrated promising results for MenACWY-CRM as indicated by robust immune responses against serogroups A, C, W-135, and Y and a well-tolerated safety profile.…”
Section: Discussionmentioning
confidence: 99%
“…7,25,26 The development of a sufficiently immunogenic vaccine to broadly protect infants from meningococcal disease has proven challenging. Recent studies in this vulnerable population have demonstrated promising results for MenACWY-CRM as indicated by robust immune responses against serogroups A, C, W-135, and Y and a well-tolerated safety profile.…”
Section: Discussionmentioning
confidence: 99%
“…First, our study is based on a single hospital and this may imply that the results may only be applicable to places with a population structure and local ecology similar to ours. However, changes in the spectrum of ABM similar to those observed in our study have been described, especially those referring to the epidemiology of meningococcal disease [2,[24][25][26]. Moreover, the pattern of population change documented in Spain, has also been reported in other Western, mainly European countries [27].…”
Section: Discussionmentioning
confidence: 57%
“…28 For the selection of test strains and calculation of possible coverage of a new vaccine, designed to cover MenB disease broadly needs comprehensive surveillance of MenB disease. The EU-IBIS collection in Europe 15 and the CDC collection in the US are representative for European and the US MenB isolates. These are very important collections for the burden of disease in these western world countries.…”
Section: 漏 2 0 0 8 L a N D E S B I O S C I E N C E D O N O T D I S mentioning
confidence: 99%
“…14 In this respect it is important to note that the majority of the sero-subtypes causing disease were shown to belong to a restricted number of infectious clones. 15 The PorA-sero-subtypes belonging to these clones are covered in NonaMen 庐 .…”
Section: Omv-based Vaccinesmentioning
confidence: 99%